Gas chromatography with glass capillary columns - Jennings, Walter, 1922- (Academic Press, 1980)
The need for this second edition is dictated by developments that have occurred in this rapidly changing field and by sins of omission and sins of commission in the first edition. Projections available at the time of this writing indicate that gas chromoatography will remain the world's most widely used analytical technique for some time.